Youth Strategies in Economic Empowerment - Hendrasto, Nur; Nuriyah, Aminah; Nurhasanah, Saniatun; Haidar, Abdullah; Maulida, Syahdatul (Tamkin Jurnal Pemberdayaan Tazkia, 2024)
The research "Youth Strategy in Economic Empowerment" thoroughly examines the strategic significance of young people in promoting economic growth, particularly within the halal industrial sector. This study emphasizes the significant contribution that young people, who constitute a crucial segment of the world population, may make to the advancement of socioeconomic development. This research uncovers the most recent developments in the halal business by means of seminars including prominent speakers like Prof. Dr. Marco Tieman. It focuses on crucial elements such as supply chains and ecosystems. The paper's conclusion underscores the significance of innovation and the contributions of young individuals, serving as inspiration for aspiring entrepreneurs in the global development of the halal industry